SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN COOK’S ASSISTANT TERBAIK MENGGUNAKAN METODE ARAS - Siregar, Victor Marudut Mulia; Sugara, Heru; Saragih, Roy Sahputra (Politeknik Bisnis Indonesia, 2025)
Selecting the right Cook’s Assistant is a critical factor in ensuring smooth restaurant operations, including at Lucky Seafood Restaurant in Pematang Siantar. The existing recruitment process often lacks objectivity and consistency, highlighting the need for a technology-based solution to improve decision-making accuracy and efficiency. This study aims to develop a Decision Support System (DSS) using the Additive Ratio Assessment (ARAS) method to assist management in selecting the most suitable candidate. The system evaluates five criteria: work experience, communication skills, and work attitude (benefit criteria), along with adaptation time and error rate (cost criteria). The ARAS method involves normalization, weighting, and the calculation of utility and utility degree values. The results indicate that among eight candidates, AC_06 ranks highest with a utility score of 1.51518, followed by AC_04 and AC_08. The implementation of this system has proven effective in reducing subjectivity, expediting the selection process, and increasing the accuracy of identifying the best candidate aligned with the restaurant’s operational needs.